Tendências na incidência e na mortalidade do câncer colorretal em uma cidade do Nordeste brasileiro - Moura, Alex Rodrigues (2020)
Colorectal and anal cancer (CCR) is a public health problem in the world and in Brazil. It has been showing an increase in incidence and mortality, and is among five most common neoplasms. Objectives: to analise trends in the incidence and mortality in Aracaju, Sergipe, between 1996 and 2015 through statistical analysis using Joinpoint Regression Program 4.7.0.0.; to determine the proportion of CCR considering topographies, histological types and sex, at the time of diagnosis; to determine the sex ration of incidence and mortality; to determine the mortality/incidence ration after diagnosis and identify geographic distribution in the city through the Kernel heat map. Methods: this is a partially ecological study of time series aggregate divided in three parts: descriptive, trend and spatial analysis. Results: out of a total of 1,435 cases, 61% correspond to women and 39% to men. Regarding deaths, women contributed with 58% and men 42%. Among the 20 – 44 year age group, for males, there was a significant growth trend, with the highest annual percent change. For women, the growth trend, with the APC observed, was the 45 and 64 years age group and all ages. Regarding mortality both genders, trends were stable in all periods studied. The adjusted incidence rate for females ranged between 11.5 and 22/100,000; males between 8.9 and 23.3/100,000, and those for mortality ranged between 2.07 and 8.47/100,000 and 3.47 and 9.24/ 100,000, respectively. The mortality/incidence ratio was around 0.4. Adenocarcinoma was the most common histological subtype. Regarding geographic distribution, there was a constancy of hotpoints in the northeast region of the municipality. Conclusion: CCR has been increasing in incidence, especially among men between 20 to 44 years, but stable in relation to mortality in Aracaju.